Deepening Understanding: Adding Privacy into a Library and Information Studies Course. Issue 1 (4th July 2021) - Ray, Emily; Feinberg, Daniel E.
ABSTRACT: This case will cover the experiences that the Online Learning Librarian (OLL) and E-resources Librarian (ERL) worked on adding a module about privacy to a 1 credit Information Literacy course at the University of North Florida (UNF). There will be a discussion of what motivated the OLL to include data privacy as a module within Canvas, how the module was implemented, and the student experience in this course. At UNF, librarians have taught undergraduates in LIS1001 "Beginning Library and Information Systems Studies since the 1980s. The course has focused on information literacy and information freedom; data privacy, however, has not been included. Despite this, many students have asked about what happens to their data submitted into UNF systems. When students enter the UNF Thomas G. Carpenter library, they must scan their student IDs, which provides the library statistical data of major, academic standing and other identifying information. In addition, all students, in person or online, must use authentication when logging into computers, into databases, when reading ebooks, etc. Since Dan Feinberg, the OLL, started working at UNF in 2017, students complained to him regarding the data necessary to attend school. These off-the-cuff discussions reflected a desire for information freedom. After discussing privacy issues, the ERL and the OLL decided to come up with a module on data privacy that would work for undergraduates in the LIS1001 course. The OLL and ERL considered what aspects of privacy to cover (i.e. how much on technology) and resources to include, focusing on materials appropriate for undergraduates and that related to their experience. The OLL developed and built a unique module in Canvas that was used already in one course and will be used in future semesters. Within this structure, students learned about privacy issues in higher education and expressed their interpretations of privacy, what it means to them, and considered what they are willing and able to sacrifice to maintain privacy as college students in 2020.